Research Skills of High School Students in STEM Learning: An Analysis Using the Research Skill Development Framework - Putri Flamonia; Lilik Hasanah; Irma Rahma Suwarma (FKIP - Universitas Riau, 2026)
Research skills are essential in science education because they enable students to formulate questions, use evidence, and construct defensible solutions, yet these skills are often reported as a single overall score. This study aimed to characterize senior high school students’ research skills across the six facets of the Research Skill Development (RSD) Framework in STEM learning. A quantitative descriptive design involved 30 tenth-grade students from a public senior high school in Indragiri Hilir Regency, Riau Province, Indonesia, who participated in a renewable-energy STEM cocurricular program. Students’ written responses from two STEM-based worksheets were assessed using an analytical rubric covering Embark and Clarify, Find and Generate, Evaluate and Reflect, Organize and Manage, Analyze and Synthesize, and Communicate and Apply. Results showed higher performance across all facets in Worksheet 2. Find and Generate increased from 63.3% to 92.1%, whereas Communicate and Apply increased from 37.8% to 85.6% and showed the highest normalized gain (g = 0.71). Embark and Clarify showed the lowest normalized gain (g = 0.45), indicating continuing difficulty in formulating focused and investigable questions. These findings suggest that authentic digital data exploration and engineering design activities supported evidence use, synthesis, and communication, while problem formulation required stronger instructional scaffolding.